1990
DOI: 10.1288/00005537-199005000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The clinical behavior of inverting papilloma of the nose and paranasal sinuses: Report of 112 cases and review of the literature

Abstract: Between 1944 and 1987, 112 patients with inverting papilloma of the nasal cavity were treated. The average duration of follow-up for this population was 6.2 years. The most common symptoms were nasal obstruction and history of previous surgery for nasal "polyps". Recurrence rates were lower when treatment consisted of lateral rhinotomy with medial maxillectomy (14%) vs. transnasal operation with a sinus procedure (35%) or transnasal operation alone (58%). Recurrence rates between men and women were not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
142
2
5

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(155 citation statements)
references
References 12 publications
6
142
2
5
Order By: Relevance
“…As other authors have repeatedly shown, 1,5,7,12,13 our series indicates that aggressive surgical procedure can reduce the recurrence rate of inverted papilloma. Our conservative-treatment group showed a somewhat higher recurrence rate (33.9 per cent) when compared with other reported conservative-treatment groups (around 18 per cent).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As other authors have repeatedly shown, 1,5,7,12,13 our series indicates that aggressive surgical procedure can reduce the recurrence rate of inverted papilloma. Our conservative-treatment group showed a somewhat higher recurrence rate (33.9 per cent) when compared with other reported conservative-treatment groups (around 18 per cent).…”
Section: Discussionsupporting
confidence: 73%
“…Because of its high recurrence rate and aggressive nature, management of inverted papilloma has changed from conservative intranasal piecemeal excision to a more aggressive wide excision by lateral rhinotomy combined with a medial maxillectomy. [4][5][6][7][8] However, some authors have reported recently that an endoscopic endonasal approach can be performed in selected cases in which tumour extension is limited. [9][10][11] Few reports have been published on the relationship between polyp and inverted papilloma, and on the treatment outcome of recurrent inverted papilloma.…”
Section: Introductionmentioning
confidence: 99%
“…Ki-67 has been utilized to demonstrate proliferating cells in G1, S, G2 and M phases of the cell cycle [15]. Ki-67 has been used to study the growth fraction and cytokinetic activity in various carcinomas [15].…”
Section: Introductionmentioning
confidence: 99%
“…Rare locations include the sphenoid sinus and frontal sinus [1][2][3][4][5]9 . In our study, the most frequent location and extension of IP was represented by involvement of both ethmoid and maxillary sinuses, in 110 cases from our series (67.90%), concurring with most authors.…”
Section: Discussionmentioning
confidence: 99%
“…This being said, tumors developing in the maxillary sinus will have to grow and extend to different close regions before expressing any discomfort to the patient, thus delaying the diagnosis. Common symptoms of IP are progressive unilateral nasal obstruction, blood mixed nasal discharge, headache, frequent throat clearing, sometimes epiphora or symptoms of sinusitis 4,5,16 . Clinical and paraclinical assessment of IP includes nasal endoscopy with anatomic macroscopic description of the tumor, imaging studies and also biopsy.…”
Section: Discussionmentioning
confidence: 99%